The Place and Position of Molana Shibli Nomani in Urdu Historiography - Islam, Rashid (sourcecoder, 2024)
Molana Shibli Nomani considered one of the important Urdu Historian in the world. He has most eminent and important position in the Historiography among the entire historian of India who wrote history in Urdu language during 19th century. Molana Shibli received his early education from different institutions. After receiving his traditional Muslim education from different renowned scholars of the time later on Shibli finally entered in the circle of Sir Syed Ahmad Khan. Shibli looked the position of Muslims and tried to boost up them again according to the glorious period of past. That’s why Shibli work on the remarkable personalities and wrote biographies i.e. Seerat ul Nabi, Al-Farooq, Al-Mamoon and Al-Ghazali etc.